Numerical simulation of the particle filtration process inside porous walls using lattice Boltzmann method. (20th July 2019) - Kong, Xiangjin; Li, Zhijun; Cai, Dong; Shen, Boxi; Zhang, Yanke
Graphical abstract: Highlights: The DDLB-CA model model is developed to investigate the particle filtration process. Non-virtual porous structure wall is generated by a new reconstruction scheme. The effects of different porous walls on the flow field are investigated. The statistical characteristics of particle deposition and distribution are studied. The dynamic evolution process of the deposited soot particles is simulated. Abstract: A domain decomposition-based lattice Boltzmann-cell automation probabilistic model (DDLB-CA model) has been developed to investigate soot particle filtration process in wall-flow diesel particulate filters. In order to obtain useful information for optimization of the porous structure, non-virtual porous walls are considered. Nine different porous walls are generated by a self-developed reconstruction scheme based on the pore size distribution (PSD) and porosity. The DDLB-CA model is validated with the results of previous studies. A clear pressure gradient and a spatial inhomogeneous velocity distribution can be seen for each porous wall. For the porous wall with the smallest mean pore size and the largest porosity, a lower initial pressure gradient and a better initial homogeneous velocity distribution can be achieved. Particles tend to deposit at the front of the porous wall with a PSD of a smaller mean pore size. Besides, particles also have an obvious tendency of depositing on the surface of narrow porous channels. Particle capture probability is obviously affected by the PSD. Therefore, adjustment of the PSD is recommended for optimization of the particle distribution and filtration efficiency. The solid nodes composed of deposited soot particles appear on the surface of narrow porous channels first and then form dendritic structures. Finally, the dendrite structures construct a bridge and block the narrow porous channel. The distributions of solid nodes are affected obviously by the structure of porous media. The locations of solid nodes affect the distribution of pressure and the uniformity of velocity distribution. The subsequent particles are more inclined to deposit at the front of the porous wall and the particle deposition efficiency η increases after the formation of solid nodes. For the porous wall with a PSD of a smaller mean pore size, the solid nodes in front of porous walls ( x/Lw  < 0) are more concentrated, which means the cake layer will form more easily.